Knowledge, Attitude, and Practices Concerning Covid-19 Preventive Measures Among Healthcare Providers in Jordan - Fayez Majed Amro RN; Ahmad Hussien Rayan RN, CNS, PhD; Nidal Fareed Eshah RN, CNS, PhD; Mohammed Sa'd ALBashtawy PhD, MPH, RN (SAGE Publishing, 2022)
Purpose This study aims to assess the knowledge, attitudes, and practices of healthcare workers toward COVID-19 preventive measures and related factors. Methods Descriptive, correlational, and cross-sectional design was used. A convenience sample of 140 Jordanian healthcare providers working in COVID-19 units from governmental hospitals completed the study during February-March 2021. A self-reported measure with three domains: knowledge (e.g., COVID-19 transmissions), attitudes (e.g., COVID-19 vaccination), and practices (e.g., handwashing) were used. An independent t-test was performed to assess the difference in knowledge, attitude, and practice depending on demographic and work-related variables, while Pearson r and multiple linear regression were performed to identify the relationships between the study variables and the predictors of COVID-19 preventive practices. Results The majority of the participants had good knowledge (81.4%), good attitude (87.1%), and satisfactory practice (77.9%). Knowledge was significantly associated with attitude and practice ( p  < .01), and attitude was significantly associated with practice ( p  < .01). There was a statistically significant difference in knowledge, attitude, and practice depending on the existence of infection control policy, availability of PPE, and receiving infection control training ( p  < .05). Predictors of COVID-19 practice included knowledge and attitude, PPE availability, and receiving training on infection control ( p  < .05). Conclusion This result might suggest that there are some gaps between knowledge, attitudes, and practices of COVID-19 preventive measures. Lack of PPE and inadequate infection control training could contribute to this gap.